Third party recognition, perceived product related risk, and perceived ease of use among the online consumer trust: The moderating role of internet experience - Nibras Mosawi; Arfan Shahzad; Abd. Ghani B Golamdin; Ahmad Tisman Pasha; Adnan Ahmed Sheikh (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
In the 21st century, the growth of internet has gained a special attention of researchers, academicians and practitioners. In today's busy and commoditized marketing environment, B2C marketers are becoming more customer-centric and making more efforts to promote their brands. An essential part of building a brand is to create a trust connection with consumers. But, assuming that, their customers make sensible decisions, B2C marketers are focusing more on business value to differentiate their products or services. In this digital era, several problems which are effecting on the trust of online consumer will be addressed in this study. The objective of current study is to investigate the impact about perceived ease of use, third-party assurance seal and financial risk on online consumer trust with the moderating influence of internet experience. The data was collected through a survey questionnaire, in which 305 students of University Utara Malaysia, University Malaysia Perlis and University Sains Malaysia has been selected randomly. Further, the study has employed quantitative, cross sectional research design. Additionally, since the measurement model has been considered as a valid and reliable, Partial Least Square - structural equation modeling (PLS-SEM) has been selected to test the hypothesis, as the major analysis technique. Therefore, the findings of current study shown that, there is a significant influence of financial risk and third party recognition on online consumer trust and also internet experience, moderates the link between financial risk and the online customer trust. However, on the other side, no significant relationship has been found between perceived ease of use and the online customer trust. In addition to this, internet experience does not moderate the relationship among perceived ease of use and online consumer trust.
Keywords: 330; internet; B2C; perceived ease of use; third-party assurance seal; financial risk; online consumer trust